UPAYA GURU DALAM MENGEMBANGKAN KETERAMPILAN SOSIAL ANAK KELOMPOK B TK MALLUSETASI KECAMATAN TELLUSIATTINGE KABUPATEN BONE - S, Srinita; Mahmud, Bonita (Institut Agama Islam Negeri Bone, 2023)
The aims of this study were 1) to determine the teacher's efforts in developing early childhood social skills in group B of the Mallusetasi Kindergarten, Tellusiattinge District, Bone Regency. 2) To find out the factors supporting and hindering the teacher's efforts in developing the social skills of Group B students of Mallusetasi Kindergarten, Tellusiattinge District, Bone Regency. This research method uses descriptive qualitative research with pedagogic and psychological approaches, to obtain the desired data using primary and secondary data. Then analyzed by: 1) Reducing the data, 2) Describing the data, 3) Drawing conclusions. The results of this study indicate that the learning process in the teacher's efforts to develop social skills of group B students of Mallusetasi Kindergarten, Tellusiattinge District, Bone Regency, namely: 1) social play 2) provides opportunities for social development 3) provides a vehicle for positive social development of children 4) provides facilities and infrastructure. Then to find out. To find out the factors supporting the teacher's efforts in developing the social skills of Group B students of Mallusetasi Kindergarten, Tellusiattinge District, Bone Regency, namely the enthusiasm that children have and the motivation that the teacher gives. The inhibiting factors experienced by teachers in developing early childhood social skills in Group B are the child's emotional state and the child's lack of attention while studying.